Seasonal Incidence of Whitefly, Bemisia tabaci (Gennadius) on Tomato in Gird Region of Madhya Pradesh - Tomar, Neha; Singh, Pradyumn; Sasode, Rajni Singh; Bhadauria, NS; Singh, UC; Seervi, Sitaram; Suman, Shivani (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present investigation was carried out during the cropping season 2022-23 and 2023-24 at Entomological Research Field, College of Agriculture, Gwalior, Madhya Pradesh, India. The objective of the investigation was to study the seasonal incidence of whitefly, Bemisia tabaci (Gennadius) on tomato in this region and to examine the influence of weather factors on its incidence. The incidence of whitefly was first observed on 51st SMW (17th - 23rd December) and the peak incidence was noted on 9th SMW (26th February - 4th March), during 2022-23 and 2023-24 cropping season. The result of correlation studies revealed maximum temperature and minimum temperature found significant positive correlation with whitefly population in both consecutive years. While, morning RH found significant negative correlation with incidence of whitefly, during 2023-24. However, evening RH found significant and negative corelation with whitefly population in both the years.